MODIFIED CEMENT SYSTEM: DURABILITY AND AESTHETICS - Mohamed, J.S.Z; Norsuzailina, Mohamed Sutan (UNIMAS, 2022)
Concrete deterioration is one of the most concerning matters in the construction world. Significant decay such as efflorescence should not be ignored. The efflorescence is a deposit of salts, usually white, formed on the surface of the concrete. The efflorescence is not a significant problem that leads to structural defects, but it can build unattractiveness to the structure, such as brick walls and concrete mortar. The way to prevent the efflorescence occurrence is by studying the results of testing such as absorption and efflorescence itself to reduce the efflorescence. The non-modified cement system can reduce efflorescence but cannot avoid it because of the reaction of cement hydration itself. This study proves that using a modified cement system such as Pulverized Fly Ash (PFA) and Polymers (water-based latex grade 29Y46), the efflorescence of the mortar can be prevented. This study proved that the modified mortar, a sample with PFA and Polymers, has higher strength, durability, and minor efflorescence than the non-modified cement system.